Particle Image Velocimetry and Proper Orthogonal Decomposition Applied to Aerodynamic Sound Source Region Visualization in Organ Flue Pipe - MICKIEWICZ, Witold (Archives of Acoustics, 2015)
The paper presents experimental results of the visualization of the nonlinear aeroacoustic sound generation phenomena occurring in organ flue pipe. The phase-locked particle image velocimetry technique is applied to visualize the mixed velocity field in the transparent organ flue pipe model made from Plexiglas. Presented measurements were done using synchronization to the tone generated by the pipe itself supplied by controlled air flow with seeding particles. The time series of raw velocity field distribution images show nonlinear sound generation mechanisms: the large amplitude of deflection of the mean flue jet and vortex shedding in the region of pipe mouth. Proper Orthogonal Decomposition (POD) was then applied to the experimental data to separately visualize the mean mass flow, pulsating jet mass flow with vortices and also sound waves near the generation region as well as inside and outside of the pipe. The resulting POD spatial and temporal modes were used to approximate the acoustic velocity field behaviour at the pipe fundamental frequency. The temporal modes shapes are in a good agreement with the microphone pressure signal shape registered from a distance. Obtained decomposed spatial modes give interesting insight into sound generating region of the organ pipe and the transition area towards the pure acoustic field inside the resonance pipe. They can give qualitative and quantitative data to verify existing sound generation models used in Computational Fluid Dynamics (CFD) and Computational Aero-Acoustics (CAA).